Pengaruh Komunikasi dan Motivasi Kerja terhadap Kinerja Karyawan di PT PLN (Persero) Unit Pelayanan dan Jaringan Padalarang Kabupaten Bandung Barat - Sri Mulyeni (Lembaga Layanan Pendidikan Tinggi Wilayah IV, 2018)
As a service provider to the community, PT PLN (Persero) always develop them selves in order to provide better service to all stakeholders. The best servicce will be realized if employees have high performance. In the reality, the performance phenomenon of employees has not been optimal. Judging from human resource management, communication and work motivation are the variables that can affect employee performance. The purpose of this study to determine the effect of communication and work motivation on employee performance at PT. PLN (Persero) Service Unit and Network Padalarang. Respondents were taken as many as 34 people, using questionnaire as an instrument to obtain data, and data analysis done descriptively and associative. The results obtained in this study is that if communication (X1) and work motivation (X2) increased then the tendency of employee performance (Y) to increase. In addition, there is influence of communication (X1) on employee performance (Y) positively and there is influence of work motivation (X2) on employee performance (Y) positively. Result of the research t test communication variable (X1) on employee performance (Y) and work motivation (X2) on employee performance (Y) has bigger value compared than. It can be concluded that H1 is accepted and Ho is rejected. Through simultaneous test, hail calculation is obtained that the value of Fcount is bigger than Ftabel so that it can be concluded that H1 is accepted and Ho is rejected, which means that the independent variable of communication (X1) and work motivation (X2) are predictors simultaneously or together have significance with the dependent variable of employee performance (Y). Thus it can be concluded that employee performance is influenced by communication and work motivation.